A comparative life cycle assessment of chalcogenide/Si tandem solar modules. (15th February 2018) - Lunardi, Marina M.; Moore, Stephen; Alvarez-Gaitan, J.P.; Yan, Chang; Hao, Xiaojing; Corkish, Richard
Abstract: Tandem technologies offer potential price reductions and higher efficiencies of PV modules. The high band gap nature of chalcogenides like CIGS, CZTS and AZTS makes them excellent materials for use on top of a Si base tandem cells. Nevertheless, along with the search for new technologies, there is also the concern about the environmental impact that its lifetime can cause. A comprehensive life cycle assessment for CIGS/Si, CZTS/Si and AZTS/Si tandem solar modules was not reported to date. This work compares the environmental impacts of Si and chalcogenide/Si tandem solar modules, assessing global warming potential, human toxicity potential (cancer and non-cancer effects), freshwater eutrophication potential, freshwater ecotoxicity potential, abiotic depletion potential and the energy payback time of these technologies. The results of this study show that compared with Si, CIGS/Si presents worse environmental impacts for most of the categories but, on the other hand, CZTS/Si and AZTS/Si present better outcomes for most of the impacts categories. We can also say that higher efficiency of these tandem technologies could potentially reverse that result. This LCA provides design advice for the R&D community, showing which structure has the best environmental outcomes and which processes should be optimized to achieve better results. Highlights: For GWP, tandem structures have better outcomes than silicon. For toxicity the main impacts come from the CdS layer. The recycling of toxic and scarce metals is important. The use of energy during the processes is alarming.